Effect of uniform inclined magnetic field on natural convection and entropy generation in an open cavity having a horizontal porous layer saturated with a ferrofluid - Gibanov, Nikita S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Al-Salem, Khaled (Taylor & Francis Inc, 2017)
Numerical analysis of natural convection combined with entropy generation in a square open cavity partially filled with a porous medium has been performed for a ferrofluid under the effect of inclined uniform magnetic field. Governing equations with corresponding boundary conditions formulated in dimensionless stream function and vorticity using Brinkman-extended Darcy model for porous layer have been solved numerically using finite difference method. An influence of key parameters on ferrofluid flow and heat transfer has been analyzed. It has been found that an inclusion of spherical ferric oxide nanoparticles can lead to a diminution of entropy generation in the case of similar flow and heat transfer structures.
Keywords: Lattice Boltzmann Simulation; Cu-Water Nanofluid; Heat-Transfer; Mixed Convection; Vertical Cylinder; Tiwari; Flow